Potential of Dried Edible Caterpillars (Lepidoptera: Saturniidae) Vending on Local Markets to Improve Mineral Suitability in the Diet of the Population in Democratic Republic of the Congo - Ombeni, Justin Birhashwirwa; Conti, Maria Vittoria; Cena, Hellas; Munyuli, Theodore (International Journal on Food, Agriculture and Natural Resources, 2024)
Insects, a traditional food in many parts of the world, are highly nutritious and especially rich in proteins and thus represent a potential food and protein source. They are rich in essential amino acids and unsaturated fatty acids and provide ample quantities of minerals such as Fe, Zn, Mn, Ca, and P essential for human health. The objective of this study was to assess the nutritional value of dried edible caterpillars with an exclusive focus on mineral content. Quantitative analysis of seven essential minerals for humans was analyzed for two dried edible caterpillars currently commercialized in Bukavu town, South Kivu province (eastern DR Congo) central market including Bunaeopsis aurantiaca (Lepidoptera: Saturniidae) and Imbrasia oyemensis (Lepidoptera: Saturniidae). Mineral content analysis of Ca, Mg, Na, Fe, Zn, and Mn were carried out using the Atomic Absorption Spectrophotometer (AAS) while the P content was analyzed using the Colorimetric method, then the mineral content was compared to the recommended daily intakes (mg/day). On a dry weight basis, we find that mineral content differed with type of caterpillar. I. oyemensis had the highest concentrations of most minerals tested compared to B. aurantiaca, which nevertheless had the greatest amount of phosphorus (P). P was significantly the most abundant mineral detected (605.70 ± 6.08 mg/100g; p < 0.001), followed by Mg and Na in I. oyemensis with 220.11 ± 6.10 mg/100g and 216.43 ± 1.08 mg/100g respectively. Oligo-minerals Zn and Fe, were the lowest in the caterpillar samples. All the edible caterpillars analyzed met the recommended daily mineral intake. The consumption of < 28 g and < 8 g of these caterpillars covers daily RNI in adults for Fe and Mn respectively. Thus, edible caterpillars in this study have shown that they can be excellent contributors to people's mineral requirements and should be sustainably utilized. Aside from direct consumption, there is a huge potential for using these caterpillars as raw material and food fortification. The mineral content of commonly eaten caterpillars was analyzed to inform consumers among indigenous populations in the Democratic Republic of Congo about the micro-nutritional quality of the insects.